2020
DOI: 10.31545/intagr/118196
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal inoculation as an alternative for the ecological production of tomato (Lycopersicon esculentum Mill.)

Abstract: The aim of study was to investigate the effect of two mycorrhizal fungus species Claroideoglomus etunicatum and Rhizophagus intraradices on the uptake of macronutrients and on the growth and yield of tomato hybrid plants cultivated in an ecological system. The experiment was carried out at an ecological farm in Grądy in the Lublin province of Poland, for three years (2015-2017). The experimental treatments included plants inoculated with Claroideoglomus etunicatum, Rhizophagus intraradices and plants without m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
(66 reference statements)
0
9
0
3
Order By: Relevance
“…This hypothesis was confirmed by Jamiołkowska et al (2008), who showed that the inoculation of seedlings with mycorrhizal fungi significantly influenced the length of tomato stems and roots. It was found that MF application to tomato roots significantly improves the physiological and morphological parameters of the cultivated plants (Jamiołkowska et al, 2020a). Thicker leaves allow for improved photosynthesis at a high radiation intensity, which explains the high variation of this feature in response to light.…”
Section: Mycorrhizae and Plant Growth Regulationmentioning
confidence: 94%
See 4 more Smart Citations
“…This hypothesis was confirmed by Jamiołkowska et al (2008), who showed that the inoculation of seedlings with mycorrhizal fungi significantly influenced the length of tomato stems and roots. It was found that MF application to tomato roots significantly improves the physiological and morphological parameters of the cultivated plants (Jamiołkowska et al, 2020a). Thicker leaves allow for improved photosynthesis at a high radiation intensity, which explains the high variation of this feature in response to light.…”
Section: Mycorrhizae and Plant Growth Regulationmentioning
confidence: 94%
“…Nutrient uptake pepper, tomato, cereals -Karaki et al, 2001;Azcón et al, 2001;Hodge et al, 2001;Liu et al, 2002;Giri and Mukerji, 2004;Govindarajulu et al, 2005;Reynolds et al, 2005;Lambers et al, 2008;Oseni et al, 2010;Wu et al, 2010;Cavagnaro and Martin, 2011;Guru et al, 2011;Alvarez et al, 2012;Tanwar et al, 2013;Motha et al, 2014;Saia et al, 2014;Wahb-Allah et al, 2014;Hart et al, 2015;Michałojć et al, 2015;Chitarra et al, 2016;Jamiołkowska et al, 2020a Photosynthesis maize, tomato, poplar Augé, 2001;Nelson and Achar, 2001;Sannazzaro et al, 2006;Colla et al, 2008;Zuccarini and Okurowska, 2008;Sheng et al, 2008;Zhu et al, 2012;Liu et al, 2015 Claroideoglomus etunicatum and Rhizophagus intraradices Growth tomato, olive Augé, 2001;Dasgan et al, 2008;Oseni et al, 2010;Guru et al, 2011;Castillo et al, 2013;Conversa et al, 2013;Tanwar et al, 2013;Khabou et al, 2014;Motha et al, 2014;Wahb-Allah et al, 2014 Yield tomato Demir, 2004;Subramanian et al, 2006;...…”
Section: Mycorrhizal Fungimentioning
confidence: 99%
See 3 more Smart Citations